Genetic characterisation and analysis of infectious bronchitis virus isolated from Brazilian flocks between 2010 and 2015. Issue 6 (2nd November 2017) - Carranza, Claudia; Astolfi-Ferreira, Claudete S.; Santander Parra, Silvana H.; Nuñez, Luis F. N.; Penzes, Zoltan; Chacón, Jorge L.; Sesti, Luiz; Chacón, Ruy D.; Piantino Ferreira, Antonio J.
ABSTRACT: 1. Infectious bronchitis virus (IBV) variants in Brazil were isolated during 2010–2015 for epidemiological and molecular analysis to characterise the different variants and perform a bioinformatic analysis to compare with sequences of variants collected over the previous 40 years. 2. Of the 453 samples examined, 61.4% were positive for IBV and 75.9% of these were considered to have the BR-I genotype and were detected in birds of all ages distributed in all five Brazilian regions. 3. The ratio of non-synonymous substitutions per non-synonymous site (dN) to synonymous substitutions per synonymous site (dS), i.e. dN/dS, revealed a predominance of codons with non-synonymous substitutions in the first third of the S1 gene and a dN/dS ratio of 0.67. Additionally, prediction of N-glycosylation sites showed that most of the BR-I variants (from 2003 to early 2014) had an extra site at amino acid position 20, whereas the newest variants lacked this extra site. 4. These results suggest that Brazilian IBV variants probably underwent drastic mutations at various points between 1983 and 2003 and that the selection processes became silent after achieving a sufficiently effective antigenic structure for invasion and replication in their hosts. Brazilian IBV genotype BR-I is currently the predominant genotype circulating in Brazil and South America.